Efektivitas Ekstrak Buah Belimbing Wuluh (Averhoa blimbi L) Dalam Menghambat Pertumbuhan Bakteri Aeromonas hydrophila Pada Ikan Mas (Cyprinus Carpio) - Siti Nurinda Buda; Yuniarti Koniyo; Arafik Lamadi (Research Review: Jurnal Ilmiah Multidisiplin, 2023)
This research aimed to determine the optimal concentration of wuluh star fruit extract in feed as an effort to prevent the growth of Aeromonas hydrophila bacteria in common carp. The study was conducted from may to june 2023. The treatments in this study consisted of different levels of wuluh star fruit extract in the feed, comprising five (5) levels:A = 0ml wuluh star fruit extract per kg of feed + injection of Aeromonas hydrophila (positive control = PC), B = 0ml wuluh star fruit extract per kg of feed ( nrgative control – NC), C = 10ml wuluh star fruit extract per kg of feed + injection of Aeromonas hydrophila, D = 15ml wuluh star fruit extract per kg of feed + injection of Aeromonas hydrophila, and E = 20ml wuluh star fruit extract per kg of feed + injection of Aeromonas hydrophila. Each treatment had three (3) replications. The common carp used was 10 cm in size, collected from a fish farm. The fish were kept in aquariums with a stocking density of 5 fish per aquarium. Prior to treatment, the fish were acclimated to the environment for 1 week. During acclimation, the fish were fed commercial pelletswith a protein content of 36% twice a day. ANOVA analysis results showed that the addition of wuluh star fruit extract significantly influenced the growth rete and survival rate of common carp, aiding in the recovery of common carp infected with Aeromonas hydrophila BACTERIA AND PREVENTING the growth of the bacteria. The optimal concentration of wuluh star fruit extract was 15ml per kg of feed to prevent the growth of Aeromonas hydrophila bacteria.